Image 443 of Theo Brown Diaries, 1949 - Brown, Theophilus (1949)
WEDNESDAY DEC. 28 1949 Bill Purcell here today. Went over drawings of new tractor and showed him movies. He said he felt it was a big step in right direction and was and example of forward thinking. He like the gas tank under platform. Henry Dreyfuss and he will be here Jan 23rd and will go over it carefully then. [Stamp: U.S. Customs Service stamp]
Keywords: diary